2021
DOI: 10.20901/ms.11.22.5
|View full text |Cite
|
Sign up to set email alerts
|

Utjecaj novih informacijsko-komunikacijskih tehnologija na obiteljski život

Abstract: Usporedno s porastom dostupnosti osobnih računala i pametnih telefona u 21. stoljeću te‏ sve većom učestalošću upotrebe interneta u svakodnevnom životu pripadnika svih generacija, značajno‏ raste i interes znanstvenika za proučavanje utjecaja novih informacijsko-komunikacijskih tehnologija‏ na obiteljski život. S obzirom na to da u Hrvatskoj nedostaje znanstvenih radova i istraživanja na tu‏ temu, cilj je ovoga preglednog rada izložiti aktualne trendove i istraživačke spoznaje u tome području,‏ produbiti razum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Authors who advocate digital optimism believe that the spread of digital technologies has a positive effect on building and maintaining social relationships in the modern world (Jones, 2002). The Internet enables networking with people with similar interests, but it can also have a positive effect on family relationships, for example, when family members do not live together (Kokorić Blažeka, 2020). In such situations, technology helps them maintain communication and closeness.…”
Section: Local Communities Social Relationships and The Spread Of Dig...mentioning
confidence: 99%
See 1 more Smart Citation
“…Authors who advocate digital optimism believe that the spread of digital technologies has a positive effect on building and maintaining social relationships in the modern world (Jones, 2002). The Internet enables networking with people with similar interests, but it can also have a positive effect on family relationships, for example, when family members do not live together (Kokorić Blažeka, 2020). In such situations, technology helps them maintain communication and closeness.…”
Section: Local Communities Social Relationships and The Spread Of Dig...mentioning
confidence: 99%
“…Research has shown that using the Internet too often leads to a decrease in communication with family members living in the same household. For example, in 2016 in Romania, 43% of respondents believed that frequent use of social media negatively affects daily communication with family members (Kokorić Blažeka, 2020). Time spent online is often a source of conflict between parents and children, but also between siblings.…”
Section: Local Communities Social Relationships and The Spread Of Dig...mentioning
confidence: 99%